Quantitative biomarkers for liver metastases: comparison of MRI diffusion-weighted imaging heterogeneity index and fluorine-18-fluoro-deoxyglucose standardised uptake value in hybrid PET/MR. Issue 9 (September 2018) - Stein, D.; Goldberg, N.; Domachevsky, L.; Bernstine, H.; Nidam, M.; Abadi-Korek, I.; Guindy, M.; Sosna, J.; Groshar, D.
Abstract : Aim: To investigate the ability of apparent diffusion coefficient (ADC) heterogeneity index to discriminate liver metastases (LM) from normal-appearing liver (NAL) tissue as compared to common magnetic resonance imaging (MRI) metrics, and to investigate its correlation with 2-[ 18 F]-fluoro-2-deoxy-d- glucose ( 18 F-FDG) positron-emission tomography (PET) standardised uptake value (SUV). Materials and methods: Thirty-nine liver metastases in 24 oncology patients (13 women, 11 men; mean age 56±13 years) with proven LM from heterogeneous sources were evaluated on a PET/MRI system. Abdominal sequences included Dixon and diffusion-weighted imaging (DWI) protocols with simultaneous PET. Tissue heterogeneity was calculated using the coefficient of variance (CV) of the ADC, and compared in LM and in NAL tissue of the same volume in an adjacent portion of the liver. The correlations between various ADC measures and PET SUV in distinguishing LM from NAL were evaluated. Results: A good correlation was found between ADCcv and SUVpeak ( r= 0.712). Moderate inverse correlation was found between ADCmin and SUVpeak ( r= –0.536), and a weak inverse correlation between ADCmean and SUVpeak ( r= –0.273). There was a significant difference between LM and NAL when ADCcv ( p< 0.0001) and ADCmin ( p= 0.001) were used. Receiver operating characteristic (ROC) analysis of SUV, ADCcv, ADCmin, and ADCmean produced an AUC of 0.989, 0.900, 0.742, and 0.623 respectively. Conclusions: The ADCcv index is a potential biomarker of LM with better correlation to 18 F-FDG PET SUVpeak than conventional MRI metrics, and may serve to quantitatively discriminate between LM and NAL. Highlights: Discriminating liver lesions from healthy tissue was investigated on a PET-MRI. ADC coefficient of variance was proposed as a heterogeneity index. Quantitative discrimination between metastases and healthy tissue was shown. ADC coefficient of variance may serve as a potential biomarker for metastases.